Endobronchial lipoma causing progressive dyspnea. (2017) - Dy, Rajany V.; Patel, Sumit; Harris, Kassem; Mador, M. Jeffery
Abstract: We describe a 63-year-old male who presented with progressive exertional dyspnea, post-obstructive pneumonia and chest CT findings of an endobronchial lesion. Bronchoscopy revealed an endobronchial lipoma, which was resected using snare electrocautery. Complete resolution of the patient's symptoms was noted following bronchoscopic resection.